Design and evaluation of BOOGIE: a collector for the analysis of cloud composition and processes - M. Vaitilingom; M. Vaitilingom; C. Bernard; M. Ribeiro; C. Verhaege; C. Verhaege; C. Gourbeyre; C. Berthod; A. Bianco; L. Deguillaume; L. Deguillaume (Atmospheric Measurement Techniques)
In situ cloud studies are fundamental to study the variability in cloud chemical and biological composition as a function of environmental conditions and assess their potential for transforming chemical compounds. To achieve this objective, cloud water collectors have been developed in recent decades to recover water from clouds and fogs using different designs and collection methods. In this study, a new active ground-based cloud collector was developed and tested for sampling cloud water to assess the cloud microbiology and chemistry. This new instrument, BOOGIE, is a mobile sampler for cloud water collection that is easy to operate with the objective of being cleanable and sterilisable, respecting chemical and microbial cloud integrity, and presenting an efficient collection rate of cloud water. Computational fluid dynamics simulations were performed to theoretically assess the capture of cloud droplets by this new sampler. A 50 % collection efficiency cutoff of 12 µm has been estimated. The collector was deployed at Puy de Dôme station under cloudy conditions for evaluation. The water collection rates were measured at 100 ± 53 mL h−1 for a collection of 21 cloud events; considering the measured liquid water content, the sampling efficiency of this new collector has been estimated at 69.7 ± 11 % over the same set of cloud events. BOOGIE was compared with other active cloud collectors commonly used by the scientific community (Cloud Water Sampler and Caltech Active Strand Cloud Collector version 2). The three samplers presented similar collection efficiencies (between 53 % and 70 % on average). The sampling process can affect the endogenous cloud water microflora, but the ATP /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="93e47eb16cb371fe6916d3191efc4f1d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1073-2025-ie00001.svg" width="8pt" height="14pt" src="amt-18-1073-2025-ie00001.png"/></svg:svg> ADP (adenosine triphosphate and adenosine diphosphate) ratios obtained from the samplers indicates that they are not stressful for the cloud microorganisms. The chemical compositions of hydrogen peroxide, formaldehyde, and major ions are similar between the collectors; significant variability is observed for magnesium and potassium, which are the less concentrated ions. The differences between collectors are the consequence of different designs and the intrinsic homogeneity in the chemical composition within the cloud system.